Happiness, Limitations Religiosity - Samuel Akpan BASSEY; Leonard NWOYE; Timothy Adie OKPE (Lembaga Sembilan Tiga Community, 2018)
Philosophers from different epochs; from Socrates to Buddha, all were more than willing to advise others on how to live a happy life. The desires that people do not necessarily require to become happy or maintain the state of happiness for considerable period are myriad. The reason for this can be seen in Aristotle’s view that the goal of the human action and thought is to be happy. Humans engage in a range of activities that make them feel happy and try to shun those that neither bring happiness nor make them feel appreciated. The thrust of this paper is to see if there are limitations to happiness? And what connection does religion has with the concept of happiness.